Let's simplify the expression \( \frac{1}{2}(9 - 7^0) + (-29)^0 \) step by step.
-
Calculate \( 7^0 \): \[ 7^0 = 1 \]
-
Next, calculate \( (-29)^0 \): \[ (-29)^0 = 1 \]
-
Now substitute these values back into the expression: \[ \frac{1}{2}(9 - 1) + 1 \]
-
Simplify inside the parentheses: \[ 9 - 1 = 8 \]
-
Now, plug it back in: \[ \frac{1}{2} \times 8 + 1 \]
-
Calculate \( \frac{1}{2} \times 8 \): \[ \frac{1}{2} \times 8 = 4 \]
-
Finally, add: \[ 4 + 1 = 5 \]
Now, let's compare it to the choices provided:
-
\( \frac{1}{2}(2) + 1 \): \[ \frac{1}{2}(2) = 1 \quad \text{and} \quad 1 + 1 = 2 \]
-
\( \frac{1}{2}(9 - 1) - 1 \): \[ \frac{1}{2}(8) - 1 \quad \Rightarrow \quad 4 - 1 = 3 \]
-
\( \frac{1}{2}(9 - 0) + 0 \): \[ \frac{1}{2}(9) + 0 \quad \Rightarrow \quad \frac{9}{2} = 4.5 \]
-
\( \frac{1}{2}(9 - 1) + 1 \): \[ \frac{1}{2}(8) + 1 \quad \Rightarrow \quad 4 + 1 = 5 \]
The only expression that is equivalent to the original expression is:
\( \frac{1}{2}(9 - 1) + 1 \).